Geriatric Syndromes and Health-Related Quality of Life in Older Adults with Chronic Kidney Disease. Issue 4 (14th April 2023) - Liu, Christine K.; Miao, Shiyuan; Giffuni, Jamie; Katzel, Leslie I.; Fielding, Roger A.; Seliger, Stephen L.; Weiner, Daniel E.
Abstract : Abstract : Key Points: In older adults with CKD, geriatric syndromes are common and are associated with reduced quality of life. Addressing geriatric syndromes could potentially improve quality of life for older adults with CKD. Background: Geriatric syndromes, which are multifactorial conditions common in older adults, predict health-related quality of life (HRQOL). Although CKD is associated with lower HRQOL, whether geriatric syndromes contribute to HRQOL in CKD is unknown. Our objective was to compare associations of geriatric syndromes and medical conditions with HRQOL in older adults with CKD. Methods: This was a secondary analysis of a parallel-group randomized controlled clinical trial evaluating a 12-month exercise intervention in persons 55 years or older with CKD stage 3b–4. Participants were assessed for baseline geriatric syndromes (cognitive impairment, poor appetite, dizziness, fatigue, and chronic pain) and medical conditions (diabetes, hypertension, coronary artery disease, cancer, or chronic obstructive pulmonary disease). Participants' HRQOL was assessed with the Short Form Health Survey-36 (SF-36), EuroQol 5-Dimensions 5-Level, and the EuroQol Visual Analogue Scale. We examined the cross-sectional and longitudinal associations of geriatric syndromes and medical conditions with HRQOL using multiple linear regression. Results: Among 99 participants, the mean age was 68.0 years, 25% were female, and 62% were Black. Participants had a baseline mean of 2.0 geriatric syndromes and 2.1 medical conditions; 49% had ≥ two geriatric syndromes and ≥ two medical conditions concurrently. Sixty-seven (68%) participants underwent 12-month assessments. In models using geriatric syndromes and medical conditions as concurrent exposures, the number of geriatric syndromes was cross-sectionally associated with SF-36 scores for general health ( β =−0.385) and role limitations because of physical health ( β =−0.374) and physical functioning ( β =−0.300, all P <0.05). The number of medical conditions was only associated with SF-36 score for role limitations because of physical health ( β =−0.205). Conclusions: In older adults with CKD stage 3b–4, geriatric syndromes are common and are associated with lower HRQOL. Addressing geriatric conditions is a potential approach to improve HRQOL for older adults with CKD. Clinical Trial registry name and registration number: NCT01462097 ; Registration Date–October 26, 2011.